The Effect of Teaching Mindfulness Techniques on Happiness, Mental Well-being and Rumination of Single Girls - Shariyati , Samira; Karimi , Behroz (Applied Family Therapy Journal (AFTJ), 2020)
Aim: The aim of this study was to investigate the effect of teaching mindfulness techniques on happiness, mental well-being, and rumination of single girls. Method: The research method was quasi-experimental with pretest-posttest design with a control group and a two-month follow-up test. The statistical population of this study was 30 single girls Over 30 years’ years who referred to Mehrsa and Jiran counseling centers in Sanandaj in the period from October to November 2016 and were randomly selected in two experimental groups (15 girls) and a control group. (15 girls) were replaced. For the experimental group, the intervention method of mindfulness techniques was performed for 8 sessions of 90 minutes and the results were analyzed using repeated-measures analysis of variance. Results: The results showed that training mindfulness techniques reduces rumination (F= 17.77, P= 0.001) and increases mental well-being (F= 16.12, P= 0.001) and happiness (F= 16.89, P= 0.001) was in the experimental group and these results were stable at the follow-up stage. Conclusion: The mindfulness treatment approach can be used as an appropriate intervention to promote the happiness of young girls in adapting to living conditions and reducing the psychological effects of celibacy.